2022
DOI: 10.1080/0886022x.2022.2107542
|View full text |Cite
|
Sign up to set email alerts
|

Predicting renal function recovery and short-term reversibility among acute kidney injury patients in the ICU: comparison of machine learning methods and conventional regression

Abstract: Background Acute kidney injury (AKI) is one of the most frequent complications of critical illness. We aimed to explore the predictors of renal function recovery and the short-term reversibility after AKI by comparing logistic regression with four machine learning models. Methods We reviewed patients who were diagnosed with AKI in the MIMIC-IV database between 2008 and 2019. Recovery from AKI within 72 h of the initiating event was typically recognized as the short-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…All data used in this study were obtained from the Medical Information Mart for Intensive Care IV (MIMIC-IV V.1.0) database—a public-access database supported by the Department of Medicine at Beth Israel Deaconess Medical Center and the Computational Physiology Laboratory at MIT, which included full information of all patients admitted to the Beth Israel Deaconess Medical Center from 2008 to 2019 (last updated in March 2021). 15 This database is freely accessible to any qualified PhysioNet user. The database consists of details of more than 500 000 hospital admissions and 70 000 intensive care unit (ICU) admissions.…”
Section: Methodsmentioning
confidence: 99%
“…All data used in this study were obtained from the Medical Information Mart for Intensive Care IV (MIMIC-IV V.1.0) database—a public-access database supported by the Department of Medicine at Beth Israel Deaconess Medical Center and the Computational Physiology Laboratory at MIT, which included full information of all patients admitted to the Beth Israel Deaconess Medical Center from 2008 to 2019 (last updated in March 2021). 15 This database is freely accessible to any qualified PhysioNet user. The database consists of details of more than 500 000 hospital admissions and 70 000 intensive care unit (ICU) admissions.…”
Section: Methodsmentioning
confidence: 99%
“…This implies that AL can have other more influential risk factors not accounted for by our variables. Previous medical studies have also shown improved AI prediction models compared to logistic regression models [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the use of administrative data to predict kidney recovery in our study, the performance of the models was fair, with AUC within 0.70. As a comparison, other studies using biomarkers to predict kidney recovery had AUC in the range of 0.66–0.79 [ 38–40 ], whereas studies using granular data from the electronic health record had AUC ranging between 0.73 and 0.83 [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%